Breaking up sitting time after stroke (BUST-Stroke). Issue 4 (June 2017) - Janssen, Heidi; Dunstan, David W; Bernhardt, Julie; Walker, Frederick R; Patterson, Amanda; Callister, Robin; Dunn, Ashlee; Spratt, Neil J; English, Coralie
Rationale: Prolonged sitting is associated with an increased risk of cardiovascular and all-cause mortality and morbidity. The metabolic and cardiovascular effects of breaking up sitting time in people with stroke are unknown. Aims and hypotheses: To determine the (i) metabolic and cardiovascular effects and (ii) safety and feasibility of an experimental protocol to break up uninterrupted sitting in people with stroke. We hypothesize that activity breaks will attenuate the effects of uninterrupted sitting on glucose and insulin metabolism, blood pressure, lipid profiles, and plasma fibrinogen and that it will be both safe and feasible. Sample size estimate: Based on previous estimates of population variability (SD 1% glucose and 30% insulin), 19 paired observations (i.e. participants) will achieve a power of 0.9 to detect a difference of 0.8% in glucose and 24% in insulin area under the curve (two-tailed testing, α = 0.05). Methods and design: People with stroke will complete three experimental conditions one week apart in randomized order: (a) uninterrupted sitting, (b) prolonged sitting with intermittent walking, and (c) prolonged sitting with intermittent standing exercises. Serial blood samples will be collected and blood pressure measured at 30 min intervals for 8 h. Study outcomes: Primary outcome will be postprandial glucose and insulin responses. Secondary outcomes will include fibrinogen concentrations, blood pressure, and adverse events and protocol feasibility. Discussion: This is the first important step in determining the cardiovascular effects of breaking up sitting time after stroke. Findings will guide future studies testing behavioral strategies to reduce sitting time for the purpose of lowering recurrent stroke risk.